2020
DOI: 10.1093/crocol/otaa050
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Drug Monitoring Is Associated With Higher Persistence to Infliximab and Adalimumab Treatment and Lower Healthcare Utilization Compared With Reactive and Clinical Monitoring

Abstract: Abstract Background Serum drug-level assays for infliximab (IFX) and adalimumab (ADA) are widely available and are most often obtained reactively, to determine the next steps in patients with loss of response. Studies done thus far on the use of these assays proactively, or during symptom remission, have had mixed results. Here we investigate persistence on therapy and healthcare utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…A question that remains to be answered is the potential utility and cost-effectiveness of proactive versus reactive TDM in the management of patients with NUI. Results obtained in IBD show greater clinical benefits and lower costs for proactive TDM compared to reactive TDM [ 86 , 94 , 95 ], probably because the proactive approach allows early intervention before a loss of response occurs and detection of immunogenicity early in treatment [ 96 ]. The potential benefits of proactive TDM of anti-TNF inhibitors in NIU need to be specifically evaluated in these patients.…”
Section: Therapeutic Drug Monitoring Of Anti-tnfα In Niumentioning
confidence: 99%
“…A question that remains to be answered is the potential utility and cost-effectiveness of proactive versus reactive TDM in the management of patients with NUI. Results obtained in IBD show greater clinical benefits and lower costs for proactive TDM compared to reactive TDM [ 86 , 94 , 95 ], probably because the proactive approach allows early intervention before a loss of response occurs and detection of immunogenicity early in treatment [ 96 ]. The potential benefits of proactive TDM of anti-TNF inhibitors in NIU need to be specifically evaluated in these patients.…”
Section: Therapeutic Drug Monitoring Of Anti-tnfα In Niumentioning
confidence: 99%
“…For IBD therapy, monoclonal antibodies against tumor necrosis factor such as infliximab, adalimumab, certolizumab pegol and golimumab have all been approved worldwide for the treatment of moderate-to-severe active Crohn's disease and/or ulcerative colitis (Argollo et al, 2020). Reactive TDM and proactive TDM have been proven as useful tools for optimizing biologic therapy, specifically anti-TNF therapy (Papamichael et al, 2019;Sparrow et al, 2020;Syed et al, 2020). While our data showed that no hospital conducted TDM for adalimumab, and only one hospital performed Infliximab TDM (data not shown).…”
Section: Analysis For Implementing Projects Of Tdm and Pgx Testingmentioning
confidence: 99%
“…This was confirmed by the pediatric PAILOT (pediatric Crohn’s disease adalimumab level-based optimization treatment) study regarding ADA in CD and 1-year steroid-free clinical remission, as well as more composite outcomes (steroid-free clinical remission + normal CRP + normal FC (fecal calprotectin)) [ 76 ], and became further validated when applied for a longer time period, far from one year. Indicatively, in a 3-year Spanish prospective trial during a median follow-up at 84 [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , …”
Section: Therapeutic Drug Monitoring (Tdm)mentioning
confidence: 99%
“…Similarly, conflicting results on proactive TDM during maintenance are displayed in retrospective observational studies. TDM-driven anti-TNF treatment (IFX or ADA) demonstrated favorable outcomes in terms of efficacy, health care utilization, surgeries, drug survival and durable drug effect not only in the short term, but also in the long term, regarding both disease types [ 79 , 80 , 81 , 82 , 83 ]. Even if applied at least once during the maintenance in patients receiving ADA, it was found to be associated with less 3-year treatment failure [ 83 ].…”
Section: Therapeutic Drug Monitoring (Tdm)mentioning
confidence: 99%